On some definite integrals connecting with infinite products and infinite series - Ramesh Kumar Muthumalai (Scientia Series A: Mathematical Sciences, 2025)
Some definite integrals involving combinations of powers, exponentials, trigonometric and hyperbolic functions are evaluated through infinite products and infinite series.